Comparative Evaluation of Salivary Flow Rate in Oral Submucous Fibrosis Patients before and after Transcutaneous Electric Nerve Stimulation: A Research Protocol - Tanaya Teredesai; Suwarna Dangore (Journal of Clinical and Diagnostic Research)
Introduction: A persistent, precancerous, and frequently debilitating condition-Oral Submucous Fibrosis (OSMF) is characterised by a slowly progressing fibrosis of the oropharynx and oral cavity. A reduction in salivary flow is one of the common symptoms experienced by sufferers. Using electric current to stimulate nerves, Transcutaneous Electric Nerve Stimulation (TENS) can be an effective method for improving salivation. TENS serves as a simple, affordable, and non invasive approach that can decrease the discomfort associated with long-lasting hyposalivation. Need of the Study: Although the effectiveness of TENS on salivary flow rate has been studied in various conditions, there is a lack of evidence or studies describing the effect of TENS on salivary flow rate in patients with OSMF. This has led to the intention of the present study. Aim: To evaluate and compare the salivary flow rate in OSMF patients before and after TENS. Materials and Methods: This prospective research investigation will be conducted in the Department of Radiology and Oral Medicine, Sharad Pawar Dental College and Hospital, Sawangi, wardha, Maharashtra, India, from February 2024 to January 2025. Patients aged between 18 and 45 years suffering from OSMF will be included in the study, evaluated based on the Inventory of Xerostomia (XI) questionnaire to confirm reduced salivation. Each patient will receive TENS treatment at 40 Hz for 15 minutes. The Modified Schirmer Test (MST) will be used to evaluate the salivary flow rate before and after TENS therapy. All findings will be recorded in a tabular format and subjected to appropriate statistical tests to evaluate the statistical significance regarding the improvement in salivary flow rate.